Mycoplasma genitalium Protein of Adhesion Induces Inflammatory Cytokines via Cyclophilin A-CD147 Activating the ERK-NF-κB Pathway in Human Urothelial Cells - Li, Lingling; Luo, Dan; Liao, Yating; Peng, Kailan; Zeng, Yanhua (Frontiers in Immunology, 2020)
Mycoplasma genitalium protein of adhesion (MgPa) plays an important role in the process of adhesion and invasion of host cells by M. genitalium, and is thus significant for its pathogenic mechanisms in host cells. Our previous study has demonstrated that cyclophilin A (CypA) is the receptor for MgPa in human urothelial cells (SV-HUC-1) and can, therefore, mediate the adherence and invasion of M. genitalium into host cells by interacting with MgPa. However, the specific pathogenesis of M. genitalium to host cells and the possible pathogenic mechanism involved in the interaction of MgPa and CypA have never been clarified. The study aimed to elucidate the mechanism involved in the pathogenicity of MgPa. Recombinant MgPa (rMgPa) induced extracellular CypA (eCypA) was detected in SV-HUC-1 cells by ELISA, and the interaction between CypA and CD147 was validated using co-localization and co-immunoprecipitation assay. In addition, both extracellular signal-regulated kinases (ERK) phosphorylation and NF-κB activation evoked by rMgPa-induced eCypA were also demonstrated. The findings of this study verified that rMgPa could induce the secretion of eCypA in SV-HUC-1 cells and thus promote the protein and mRNA expression of IL-1β, IL-6, TNF-α and MMP-9 via CypA-CD147 interaction and thus activating ERK-NF-κB pathway, which is beneficial to elucidate the pathogenesis and possible pathogenic mechanism of M. genitalium to host cells